How do neurons live long and healthy? The mechanism of neuronal genome integrity - Ihara, Dai; Rasli, Nur Rasyiqin; Katsuyama, Yu (Frontiers in Neuroscience, 2025)
Genome DNA of neurons in the brain is unstable, and mutations caused by inaccurate repair can lead to neurodevelopmental and neurodegenerative disorders. Damage to the neuronal genome is induced both exogenously and endogenously. Rapid cell proliferation of neural stem cells during embryonic brain development can lead to errors in genome duplication. Electrical excitations and drastic changes in gene expression in functional neurons cause risks of damaging genomic DNA. The precise repair of DNA damages caused by events making genomic DNA unstable maintains neuronal functions. The maintenance of the DNA sequence and structure of the genome is known as genomic integrity. Molecular mechanisms that maintain genomic integrity are critical for healthy neuronal function. In this review, we describe recent progress in understanding the genome integrity in functional neurons referring to their disruptions reported in neurological diseases.